2019
DOI: 10.1159/000502549
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life Concerns in Patients with Uveal Melanoma after Initial Diagnosis

Abstract: Background: Patients with uveal melanoma (UM) are known to have quality of life (QOL) issues after treatment, but QOL concerns after initial diagnosis are ill-defined. Objectives: We studied the QOL concerns of patients with UM after initial diagnosis to identify factors associated with QOL. Method: Between September 2011 and May 2016, UM planning to undergo radiotherapy completed the European Organization for Research and Treatment of Cancer (EORTC) core quality of life questionnaire (QLQ)-C30, as well as the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
15
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(21 citation statements)
references
References 23 publications
4
15
0
1
Order By: Relevance
“…Our results from the baseline assessments (T0) were generally consistent with previous studies that reported pre-treatment data [7,9]. In our cohort, the pre-treatment status, measured with the global QOL and all the functional subscales, except for "social functioning", was similar to findings by Barker et al, Suchocka-Capuano et al, and van Beek et al [7,9,10] (see also Table 5). The more severe effects on "social functioning" observed in our cohort may reflect the national characteristics observed in the QLQ-C30 for the German norm population, as described by Nolte et al [29].…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Our results from the baseline assessments (T0) were generally consistent with previous studies that reported pre-treatment data [7,9]. In our cohort, the pre-treatment status, measured with the global QOL and all the functional subscales, except for "social functioning", was similar to findings by Barker et al, Suchocka-Capuano et al, and van Beek et al [7,9,10] (see also Table 5). The more severe effects on "social functioning" observed in our cohort may reflect the national characteristics observed in the QLQ-C30 for the German norm population, as described by Nolte et al [29].…”
Section: Discussionsupporting
confidence: 91%
“…Only a few studies have focused on the short-term treatment-related impact of primary UM therapy [7,10,27,28]. Our results from the baseline assessments (T0) were generally consistent with previous studies that reported pre-treatment data [7,9]. In our cohort, the pre-treatment status, measured with the global QOL and all the functional subscales, except for "social functioning", was similar to findings by Barker et al, Suchocka-Capuano et al, and van Beek et al [7,9,10] (see also Table 5).…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations